The Effect of Carbon Nanotube Composite Addition on Biomass-Based Supercapacitor - Widiatmoko, Pramujo; Devianto, Hary; Nurdin, Isdiriayani; Yandra, Ridho Eka (Journal of Engineering and Technological Sciences, 2016)
Electric vehicles are set to become a most attractive alternative transportation mode due to their high efficiency and low emission. Electric vehicles require an efficient energy storage system, e.g. a supercapacitor. Coconut shells have high lignocellulosic content and are not being fully utilized in Indonesia. The lignocellulose could be converted into activated carbon for use as the electrode on a hybrid supercapacitor. This research focused on studying the effect of the addition of carbon nanotube (CNT) composite to porous graphene-like nanosheets (PGNS) as the electrode on a hybrid supercapacitor. The PGNS and CNT composite were synthesized via simultaneous activation and carbonization. Nickel oxide was used as the counter electrode. The CNT composite had a large surface area of 1374.8 m2g-1, pore volume of 1.1 cm3g, and pore size of 3.2 nm. On the other hand, the PGNS had a surface area of 666.1 m2g-1, pore volume of 0.47 cm3g, and pore size of 2.8 nm. The electrode pair between the NiO and the activated carbon achieved 5.69 F/g and 94.1% cycle durability after 10 charging and discharging cycles. The composite had an energy density of 0.38 W h kg-1. The aim of this research was to provide an alternative formula for producing high-performance supercapacitor materials.